The Brand Italy in the Age of On-Line Reproduction - Dainotto, Roberto (Cinergie – Il Cinema e le altre Arti, 2020)
The essay looks at the production, distribution, and consumption of the Italian novel in the global editorial market in the context of what Mark McGurl has called “the age of Amazon.” By drawing from studies on so-called “platform capitalism,” but also from those concerning the restructuring of the editorial market, the essay considers the increasing importance of branding, and in particular of national brands, in the editorial policies of the last two decades.